'I am still confused as to what caused the problem': Perceptions of mothers on communication regarding newborn illness and death in Northern Ghana. Issue 12 (2nd December 2019) - Geerlings, Emily; Kaselitz, Elizabeth; Aborigo, Raymond A.; Williams, John; Youngblood, Jessica; Avrakotos, Avery; Chatio, Samuel; Moyer, Cheryl
ABSTRACT: Neonatal morbidity and mortality remain a significant challenge in Ghana. Given the relationship between care-seeking and understanding of illness, this study aimed to explore mothers' perceptions of the cause of illness and/or death in Northern Ghana. All neonatal deaths and near-misses (babies who survived a life-threatening complication) in 2015 and 2016 were identified through a community – and facility-based surveillance system. Mothers of the deceased or ill infants participated in open narrative qualitative interviews. Narratives that included discussion of whether the mother understood what caused the baby's illness or death were analysed. Interviews with 155 mothers included discussion of their perception of the cause of newborn illness or death. Of the 155 interviews, 108 interviews involved mothers whose babies died, and 47 interviews involved mothers whose newborns survived a life-threatening illness, a neonatal 'near-miss'. Very few expressed a clear understanding of the cause of death or illness. Those mothers who did not understand were either not told or did not understand the cause of illness or death. Newborn health outcomes may be improved by increased maternal awareness and understanding of neonatal illnesses. Future interventions need to address communication issues that impair mothers' understanding, facilitate recognition of danger signs, and prompt timely care-seeking.